The Heterogenization Of Sulfanilic And Sulfonic Acids And Their Catalytic Activity In The Liquidphase Alkylation Of Phenol - Hussein Ali, Tammar (2011)
The new mesoporous silica modified with sulfanilic and sulfonic acids was synthesized by using rice husk ash (RHA) as the silica source.